EFFECT OF SILDENAFIL CITRATE ON THE BODY WEIGHT, BLOOD GLUCOSE AND WHITE BLOOD CELL COUNT DURING WOUND HEALING PROCESS IN DIABETIC RATS - Ngulde SI; Umaru B; Mahre MB; William A; Agbutun PA; Midda YH; Atela PE; Daniel HM; Giwa-Imam LN (Ntec Specialist, 2016)
Background: Diabetes mellitus is a chronic metabolic disorder with major complication of delayed wound healing. Objectives: The purpose of this study was to evaluate the effect of sildenafil on blood glucose level, body weight and leucocyte count during wound healing in diabetic rats. Method: Forty-two Albino rats randomly divided into 7 groups of 6 rats per group were treated orally with sildenafil (50 mg/kg) for 21 days and/or single dose of intraperitoneal injection of insulin (10 I.U.). Before treatments, diabetes was induced in groups A, B, C and D by a single intraperitoneal injection of alloxan (130mg/kg) and a square-shaped wound measuring 1.5cm was created under anesthesia on the dorsum of rats in all groups except group G. The rats in group A were treated with sildenafil citrate orally at the dose rate of 50 mg/kg body weight for 21 days and the rats in group B were treated with insulin injection of 10 international units once and sildenafil citrate as in Group A. The rats in group C were treated with only insulin injection of 10 international units once and the rats in group D were treated with only distilled water. Groups E and F were nondiabetic rats with wounds similar to those of diabetic rats in the previous groups and each rat in group E was also treated with sildenafil citrate as in Group A and those in group F were treated with only distilled water. The rats in Group G were normal rats without wound treated with sildenafil citrate as in Group A. Data collected were analysed using SPSS version 20. Results: The results indicated that sildenafil causes a nonsignificant (P greater than 0.05) decrease in the blood glucose of diabetic rats, a significant (P less than 0.05) increase in the leucocyte count and a significant decrease (p less than 0.05) in the rate of percentage decrease in body weight. Conclusion: Sildenafil may have the potential of reducing the rate of body weight loss in diabetic rats (with or without wound) receiving insulin treatment